IN VITRO TREATMENT OF Centrosema pubescens (Benth.) WITH SULFUR WATER AND SHEEP MANURE - Kaunang Ch.L.; Pudjihastuti E.P. (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
This study was aimed to evaluate the in vitro Centrosema pubescens response treated with sulfur water and sheep manure. The experiment was conducted at Agrostology Laboratory, Department of Animal Nutrition Science, Faculty of Animal Husbandry, Sam Ratulangi University Manado. Randomized group design of 2 x 5 factorial patterns with three repetitions based on the rumen liquid collecting time was used in this research. There were two factors in this experiment; sheep manure and sulfur water. The first factors consisted of 0 ton/ha manure (A1) and 25 ton/ha manure (A2). The second factor was sulfur water that divided into 5 levels; 0% (B1), 25% (B2), 50% (B3), 75% (B4) and 100% (B5). Variables measured in this research were dry matter digestibility (DMD), organic matter digestibility (OMD), ammonia (NH3) and Volatile Fatty Acid (VFA). In vitro nutritional evaluation performed with all variables showed both factors (sulfur water and sheep manure) had significant differences (p < 0.001) and had no significant effect (p < 0.05) on each variable. Interaction of both factors was very significant (p < 0.01) ontotal VFA and DMD. From this study it can be concluded that production of NH3, VFA, total DMD and OMD showed an optimal result if treated with 25 ton/ha of sheep manure and 50% sulfur water (39.25 ppm). Keywords: Centrosema pubescens, sulfur water, sheep manure